The Effectiveness Of TPACK-Oriented Interactive Learning Media on Fourth Grade Learning Outcomes at UPT SD Negeri 183 Gresik - Lifiyatul Handayani; Rulyansah, Afib; Nafiah; Hartatik, Sri (Universitas Nahdatul Ulama Surabaya, 2022)
The purpose of this study was to determine the effectiveness of TPACK-oriented interactive learning media on the learning outcomes of fourth-grade students of UPT SD Negeri 183 Gresik. This research is experimental research with a quantitative approach. The research design used is one group pretest-posttest. Data analysis in this study is a paired sample T-test parametric analysis. The subjects of this study were 32 graders of UPT SD Negeri 183 Gresik. The results showed that there were differences between student learning outcomes before and after using TPACK-oriented interactive learning media. Student learning outcomes obtained at the time of the pretest still did not meet the KKM value set by the school. The average student pretest learning outcomes are 33.75. Student learning outcomes at the posttest showed an average increase to 85.63. Based on the results of the statistical output of the paired T-test, it shows sig(2 tailed) 0.000 < 0.05. In this case, it can be concluded that Ha is accepted, meaning that TPACK-oriented interactive learning media is effective in the learning outcomes of fourth-grade students of UPT SD Negeri 183 Gresik. Keywords: Learning Outcomes, Learning Media, TPACK